2020
DOI: 10.1111/iej.13435
|View full text |Cite
|
Sign up to set email alerts
|

Irisin promotes odontogenic differentiation and angiogenic potential in human dental pulp cells

Abstract: Aim To determine whether irisin, a newly discovered myokine that links exercise‐induced and metabolic homeostasis, is able to promote odontogenic differentiation and angiogenesis in human dental pulp cells (HDPCs). Methodology Cell viability in the presence of irisin was measured. Real‐time PCR and Western blot analysis were performed to evaluate the expression levels of irisin, odontogenic and angiogenic markers. The involvement of mitogen‐activated protein kinase (MAPK) and the protein kinase B (Akt) signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…MAPK signaling cascades have been proven to be related to a diverse array of cellular programs which include cellular migration, proliferation, differentiation, and apoptosis [ 35 , 36 ]. Our recent publication has demonstrated that the MAPK signaling pathway can positively influence odontogenic differentiation of HDPCs [ 21 , 37 , 38 ]. Results of the present showed that icariin increased phosphorylation levels of JNK, p38, and ERK within 10 min of induction.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling cascades have been proven to be related to a diverse array of cellular programs which include cellular migration, proliferation, differentiation, and apoptosis [ 35 , 36 ]. Our recent publication has demonstrated that the MAPK signaling pathway can positively influence odontogenic differentiation of HDPCs [ 21 , 37 , 38 ]. Results of the present showed that icariin increased phosphorylation levels of JNK, p38, and ERK within 10 min of induction.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence suggests that recreational physical activity may have a protective effect on periodontal health [60,61]. Indeed, current in vitro studies reveal the involvement of irisin in differentiation, growth, and migration, as well as extracellular matrix formation in various dental cell lines [62][63][64][65][66][67][68][69][70][71][72]. It has been reported that the p38 MAPK and AKT signaling pathways are involved in irisin's effects [62,65,72].…”
Section: Irisin and Oral Healthmentioning
confidence: 99%
“…It has been studied for its potential health benefits, including its ability to increase energy expenditure, reduce fat mass, and improve metabolic health [ 87 ]. Son et al investigated and demonstrated that myokine Irisin promoted odontogenic differentiation of DPSCs by inducing mineralized nodule formation, enhancing ALP activity, and upregulating odontogenic markers [ 25 ]. Moreover, the researchers evaluated a significant increase in DPSC migration through scratch wound tests.…”
Section: Differentiative Role Of Natural Molecules In Dpscsmentioning
confidence: 99%
“…Irisin ( Figure 3 ), a myokine recently identified, stimulates migration, growth, osteogenic differentiation of periodontal ligament cells (PDLCs), and odontogenic differentiation of DPSCs [ 25 , 125 ]. An important role of irisin has been demonstrated in bone remodeling and in fracture healing [ 126 , 127 , 128 , 129 ].…”
Section: Differentiative Role Of Natural Molecules In Dbscsmentioning
confidence: 99%